Pengembangan Bahan Ajar Buku Cerita Bergambar Berbasis Kearifan Lokal dalam Meningkatkan Ecoliteracy Siswa Sekolah Dasar - Risnawati, Elis; Saepurokhman, Asep; Budiman, Arip (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to develop teaching materials in the form of a picture book based on local wisdom to enhance the ecoliteracy of elementary school students. The background of the research is the low environmental awareness among students, as reflected in environmentally unfriendly behaviors, such as littering and unhealthy eating habits. Therefore, introducing local food and the importance of environmental conservation through picture books is considered effective, as it helps students relate the stories to their daily lives. The research method used is Research and Development (R&D) involving 78 students from three schools in Sumedang Regency. The product developed, a picture book titled Bubur Suro Tradisi Masyarakat Rancakalong, was proven effective in improving students' ecoliteracy. Data collection was conducted through Likert scale questionnaires, readability analysis, and cognitive learning tests. The results show that the teaching material is valid with an expert score of 89% and a readability level of 91%. The product's effectiveness is also evident from the improvement in students' ecoliteracy on the cognitive aspect, with an average N-Gain of 82.5%. It is recommended that schools integrate these local wisdom-based teaching materials into learning to sustainably improve students' ecoliteracyKeywords: Teaching Materials, Picture Book, Local Wisdom, Ecoliteracy, Elementary School Students.